Critique and Argumentation: Rethinking Antisemitism as Common Sense - Boukala, Salomi (The Greek Review of Social Research, 2025)
Based on the Aristotelian tradition and the Critical Discourse Studies roots on critique, I introduce a Discourse Argumentative Approach (DAA) that focuses on the examination of the decryption of political arguments that appeal as common sense. In particular, this paper seeks to demonstrate through a reflexive approach that the integration of CDS with argumentation theory not only enhances analytical rigor by mitigating the risk of interpretive bias, but also challenges the analyst’s own ideological assumptions and epistemic positioning. To do so, I utilize the DAA to examine in depth the discursive normalization of antisemitism as a form of "common sense" knowledge.